THE IMPACT OF THE UNIVERSITY SUBCULTURE ON LEARNING ENGLISH AS A SECOND LANGUAGE - Chandradasa, Shavindra; Jayawardane, Dimuthu (PEOPLE: International Journal of Social Sciences, 2017)
In Sri Lanka, learning English, as a second language considered essential for the undergraduates. However, many of the undergraduates in the Faculties of Humanities and Social Sciences suffer due to their inability to use the language accurately. Analyzing more, the university subculture, which considers as the essence of the university students appears to play a decisive role in their language learning process. Hence, this study was designed to explore the impact of the university subculture on learning English as a second language. The researcher has selected the Faculty of Humanities and Social Sciences, University of Ruhuna, Sri Lanka for the investigation. Questionnaires were used to collect quantitative data whereas; in-depth interviews and focused group interviews have been used as tools to gather qualitative data. The findings revealed that the university subculture exercises sever negative impact on learning English as a second language. Such negativity was created mainly due to the socio-cultural factors associated with English. It is the sociolinguistic importance placed on English, which has made learning English more than just learning a second language. Further, the language issues related to the primary and secondary education and certain institutional shortcomings appeared to facilitate the subculture to control the students, as it wishes. The future research implications are also discussed.